2020
DOI: 10.3390/cancers12092353
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Mutant KRAS Detection from Pancreatic Secretions for the Diagnosis of Pancreatic Cancer: A Meta-Analysis

Abstract: This meta-analysis aims to identify the diagnostic accuracy of mutations in the Kirsten Rat Sarcoma (KRAS) oncogene in the diagnosis of pancreatic ductal adenocarcinoma (PDAC). The survival of PDAC remains poor often due to the fact that disease is advanced at diagnosis. We analysed 22 studies, with a total of 2156 patients, to identify if the detection of KRAS mutations from pancreatic exocrine secretions yields sufficient specificity and sensitivity to detect patients with PDAC amongst healthy individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…This could be used in detecting those patient population with unnormal cross‐sectional imaging. Recently, a diagnostic meta‐analysis of Mutant KRAS Detection in Pancreatic Secretions extracted 22 studies which demonstrated that testing of mutant KRAS can be applicable to a patient population at high risk of PDAC but with normal cross‐sectional imaging, which made up the rest part of our research in differentiating high‐risk healthy controls from PC 41 . Therefore, combining the detection of both biomarkers may help in separating PC from other situations, including benign diseases and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be used in detecting those patient population with unnormal cross‐sectional imaging. Recently, a diagnostic meta‐analysis of Mutant KRAS Detection in Pancreatic Secretions extracted 22 studies which demonstrated that testing of mutant KRAS can be applicable to a patient population at high risk of PDAC but with normal cross‐sectional imaging, which made up the rest part of our research in differentiating high‐risk healthy controls from PC 41 . Therefore, combining the detection of both biomarkers may help in separating PC from other situations, including benign diseases and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that promising specificity will help decrease unnecessary inspection or treatment which may result in infection or risk of metastasis. As previously reported, the mutant KRAS is of high specificity, however, its sensitivity is varied widely between studies as NPTX2 which may limited the application in the clinical practice 41 . Furthermore, combining with other investigation method would make it more suitable to be a screening test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylated DNA: Mutations in the KRAS oncogene are present in over 90% of resected PC specimens, with the vast majority of these mutations occurring in KRAS codon 12. A recent meta-analysis published by Patel et al [ 374 ], encompassing 22 studies aimed to assess the diagnostic accuracy of mutant KRAS detection from pancreatic secretions (mucus, secretions and juice) for the diagnosis of PC. They reported a wide variation in sensitivity (38%-89%) and specificity (13%-100%) for the diagnosis of PC through KRAS mutation testing in pancreatic secretions, with significant heterogeneity in diagnostic accuracy across the included studies.…”
Section: Pancreatic Juice Biomarkersmentioning
confidence: 99%
“…They reported a wide variation in sensitivity (38%-89%) and specificity (13%-100%) for the diagnosis of PC through KRAS mutation testing in pancreatic secretions, with significant heterogeneity in diagnostic accuracy across the included studies. They also assessed whether KRAS mutation detection would be beneficial in diagnosing PC in a screening population, which similarly returned a sensitivity ranging from 21%-86%, however specificity improved remarkably to 82%-100%[ 374 ]. In addition to KRAS, Methylated ppENK and p16 were reported to be present in pancreatic juice in 90.9% and 18.2% respectively of patients diagnosed with PC, and due to normal pancreatic juice not containing methylated forms of this DNA, their presence was postulated to suggest the presence of PC[ 375 ].…”
Section: Pancreatic Juice Biomarkersmentioning
confidence: 99%